Regeneration and Reusability of Bleaching Earth as a Sustainable Material for Tartrazine Yellow (E102) Removal: Insights into Kinetic Mechanisms - Chaida Butumap Ngolong Ngwethe; Gervais Kounou Ndongo; Donald Raoul Tchuifon Tchuifon; Cyrille Ghislain Fotsop; Dave Sanchez Mouafo Dongmo; Urselin Roland Noumsi Foko; Lynda Nathalie Nkom Soue; Melea Charles Kede (Sustainable Chemical Engineering, 2024)
Anionic dyes, like tartrazine, have harmful effects on aquatic life and humans and therefore, their elimination from industrial effluents must be taken very seriously. The removal of tartrazine yellow from wastewater was achieved using adsorption as an economical and effective treatment approach. The use of regenerated bleaching earth and regenerated bleaching earth modified with urea as adsorbents for tartrazine yellow from simulated wastewater formed the basis of this study. The sorption process was conducted in batch mode with different process parameters. Fourier transform infrared spectrophotometry (FTIR) and X-ray diffraction analyses of the adsorbent material demonstrated the presence of surface functional groups, while scanning electron microscopy revealed a porous structure. At a pH of 3, with an adsorbent dosage of 50 mg and a dye concentration of 50 mg/L, the highest dye uptake was achieved with an adsorption efficiency of 48%. The models that best described the kinetics were the pseudo-first-order, pseudo-second-order, and Elovich models (R2 > 0.95). The dye adsorption process took 140 minutes to reach equilibrium. The results of the sorption study demonstrated competition between chemisorption and physisorption, and showed that bleaching earth can be successfully regenerated and used as an efficient sorbent for eliminating tartrazine yellow from aqueous solutions.